Does Young Maternal Age Have Any Adverse Effect on Maternal and Fetal Health? A Retrospective Case Control Study - Erdem Sahin; Yusuf Madendag; Mefkure Eraslan Sahin; Ilknur Col Madendag; Gokhan Acmaz; Iptisam Ipek Muderris (Medical Network, 2018)
Objective: To reveal whether adolescent mothers are at higher risk of poor fetal and maternal outcomes compared with non-adolescent mothers. Study Design: 426 nulliparous women having a single pregnancy and gave birth with a birth-weight >500g or >24 weeks' gestation were included. Participants were divided into three groups. 1. Group consisted of adolescents between ages of 16-17(n=56), 2. Group 18-19 ages(n=185) and 3. Group 20-24 ages(n=185). Adverse maternal and fetal outcomes compared among groups. Results: The mean maternal age was 16.6(±0.40), 18.1(±0.55), 22.6(±0.60) in groups, respectively. Antenatal visits number, smoking status, vaginal delivery, emergency cesarean delivery rates (fetal distress or cephalopelvic disproportion), perineal infection, postpartum hemorrhage, transfusion requirement, maternal death were not statistically significant among groups (p=0.871, p=0.935, p=0.450, p=0.961, p=0.737, p=0.112, p=0.996, p=0.859 and p=1, respectively). Induction of labour, delivery<37 weeks, low birth weight (<2500g), admission to NICU, meconium-stained amniotic fluid, severe neonatal conditions, respiratory distress syndrome, hypoxic ischemic encephalopathy, neonatal death rates were not statistically significant among groups (p=0.187, p=0.560, p=0.408, p=0.347, p=0.901, p=0.605, p=1, p=1 and p=1, respectively). Conclusions: The data from the present study indicates that when the adolescent period is grouped not as a whole but within itself, especially low gynecological age is associated with increased adverse fetal outcomes, and it does not carry any risk for the mother. Pregnancy in adolescents aged 18-19 years does not constitute a risk for both mother and child. If it is thought that an adolescent pregnant woman can not give birth vaginally, the cesarean ratio will increase unnecessarily. Hence maternal age should not be a criterion singly for cesarean delivery.